2021
DOI: 10.2147/jpr.s319195
|View full text |Cite
|
Sign up to set email alerts
|

Overall Reporting Descriptions of Acupuncture for Chronic Pain in Randomized Controlled Trials in English Journals

Abstract: Background Whether the clinical effect of acupuncture in chronic pain is effective has always been a hot topic of research, which has a great relationship with the overall reporting descriptions of acupuncture, especially the sham acupuncture intervention. To confirm the effectiveness of acupuncture, more clinical studies are often required. Therefore, it is necessary to report high-quality and complete descriptions of acupuncture in clinical trials. This study aims to assess the overall reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Previous researchers have evaluated the reporting quality in RCTs concerning various diseases such as cancer30 and its complications,31 stroke and post-stroke rehabilitation,32 33 pain,34 35 primary insomnia,36 diabetes,37 chronic obstructive pulmonary disease,38 herpes zoster39 and vascular dementia40 among different languages 41. A systematic review by Ma et al 27 investigated published RCTs between 2004 and 2012 in China and found that the reporting of the sample estimate (1.2%), ethical committee approval (less than 1%) and conflicts of interest (0%) was inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have evaluated the reporting quality in RCTs concerning various diseases such as cancer30 and its complications,31 stroke and post-stroke rehabilitation,32 33 pain,34 35 primary insomnia,36 diabetes,37 chronic obstructive pulmonary disease,38 herpes zoster39 and vascular dementia40 among different languages 41. A systematic review by Ma et al 27 investigated published RCTs between 2004 and 2012 in China and found that the reporting of the sample estimate (1.2%), ethical committee approval (less than 1%) and conflicts of interest (0%) was inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…The trial was conducted and reported following the Consolidated Standards of Reporting Trials and Standards for Reporting Interventions in Clinical Trials of Acupuncture. [25]…”
Section: Methodsmentioning
confidence: 99%
“…In general, the needling amplitude is most closely related to the stimulation intensity of acupuncture, and many acupuncturists adjust the intensity of stimulation by changing the needling amplitude. Some results of RCTs suggested that a greater needling amplitude may exerted better pain-relieving effects in neuromusculoskeletal disorders than a smaller amplitude ( Zhang et al, 2021 ). For instance, the pressure pain threshold in a 10 cm needling amplitude increased higher than that in a 3 cm needling amplitude ( Itoh et al, 2011 ).…”
Section: Stimulation Parameters Of Ma For Selectionmentioning
confidence: 99%